Duration of sweep gas off trial for weaning from venovenous extracorporeal membrane oxygenation - Soo Jin Na; Hee Jung Choi; Chi Ryang Chung; Yang Hyun Cho; Kiick Sung; Jeong Hoon Yang; Gee Young Suh; Joong Hyun Ahn; Keumhee C. Carriere; Kyeongman Jeon (Therapeutic Advances in Respiratory Disease, 2019)
Background: No data are available on the duration of time needed to assess the adequacy of lung function after stopping sweep gas for weaning of venovenous extracorporeal membrane oxygenation (ECMO). The objective of this study was to investigate changes in arterial blood gases (ABGs) during sweep gas off trials in patients receiving venovenous ECMO. Methods: Data on patients receiving venovenous ECMO, with a weaning trial at least once, were collected prospectively from January 2012 through December 2017. Serial changes in ABGs during sweep gas off trial and clinical outcomes after weaning from venovenous ECMO were evaluated. Results: Over the study period, 192 sweep gas off trials occurred in 93 patients: 115 (60%) failed and 77 (40%) were successful. During the trial, significant changes in blood gases were observed within 1 h in all patients. When serial ABGs were compared according to trial off results, there were no significant differences in the pH, PaCO 2 , and HCO 3 − trends across time points between successful and failed trials. However, PaO 2 (70.6 versus 93.4 mmHg), SaO 2 (91.9 versus 95.2%), and PaO 2 /FiO 2 ratio (164.0 versus 233.4) were significantly lower in failed trials than successful trials within 1 h after stopping sweep gas. After 2 h of trial off, no significant change in blood gases was observed until the end of the trial. Conclusions: No change in blood gases was observed 2 h after stopping sweep gas in patients receiving venovenous ECMO. Based on our institutional experience, however, we suggest monitoring for 2 h or more after stopping sweep gas flow to assess if patients are ready for decannulation. The reviews of this paper are available via the supplemental material section.